Optimal control of Lantana camara: an entropy-based sustainable strategy - Kumar, Shyam; Mishra, Preet; Singh, R. K. Brojen (Frontiers in Ecology and Evolution, 2026)
Framing control policies to mitigate the impact of invasive plants on indigenous biodiversity within the Sustainable Development Goals (SDG) framework is the primary objective of this work. Using reported ecological dynamics of the invasive species Lantana camara, we develop a minimal three-species network model, where each node follows generalized Lotka-Volterra (GLV) dynamical equations. Employing Lie algebra and network control theory, we establish the model’s controllability and accessibility criteria. Through nonlinear optimization programming, we derive sustainable policies for controlling abundances of Lantana camara. We have also used Shannon entropy as an indicator to assess the sustainability of these optimal policies. The analysis of the sensitivity measured using this technique reveals that the control strategy is critically dependent on the ratio of the intrinsic growth rates of the Lantana camara and the control plant. Thus, we get a modular algorithmic decision support mechanism for designing control policies to manage Lantana camara abundances.